Investigation of self-perception and individual characteristics in relation to gender and professional training in late adolescence: Turkish University students - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
Background: In late adolescence, the adolescents show effort to get to know themselves better and unify their personality through different routes. Gender and professional training is significant in developing self perception and individual characteristics as well as social comparison, which represents one of these routes. Objective: The current trial was performed to investigate the association between self-perception and the individual characteristics in university students in late adolescence, thereby providing an assessment with respect to gender and professional training. Method: The study population consisted of the students at a state university and 833 students, who were selected via simple randomized sampling, represented the study sample. Data were collected using Data Forms, the Sociotropy-autonomy scale (SAS) and the Social Comparison Scale (SCS) and assessed by percentage, standard deviation, Pearson's correlation analysis, t-test, one-way ANOVA and the Bonferroni tests. Results: The mean age of the participating students was 20.97 +/- 1.86 and 67.3% were females (n=561). 34.9% of the participants were medical students (n=291). The mean SCS score, the mean sociotropy score of SAS and the mean autonomy score was 81.29 +/- 15.4, 65.22 +/- 16.8 and 72.37 +/- 16.3, respectively. While a positive significant correlation was detected between the individual achievement sub-dimension (r=.159; p<0.01) and SCS and autonomy (r=.074; p<0.05), a negative significant correlation was detected between the sociotropy sub-dimensions of disapproval anxiety (r=.098; p<0.01) and pleasing others (r=-.088; p<0.05). Gender was observed to be significantly associated with SCS (F=24.12; p=0.000), Sociotropy (F=5.11; p=0.024), Autonomy (F=15.64; p=0.000). There was a significant difference between the adolescents' mean self-perception score (SCS) and the field of training (F=3.96; p=0.008), and between the professional training and the mean sociotropy dimension score (F=10.94; p=0.000). Conclusion: The results revealed that the university students in late adolescence exhibited moderately sociotropic personality characteristics and an above-moderate level of autonomous personality; self-perception was observed to have a positive correlation with autonomous personality characteristics and a negative correlation with sociotropic personality characteristics. Gender and professional training were detected to have an influence on self perception and personality characteristics.
Keywords: Late adolescence; self-perception; sociotropy-autonomy; SOCIOTROPY-AUTONOMY; PERFORMANCE; DIMENSIONS